2011
DOI: 10.1097/gme.0b013e318219d791
|View full text |Cite
|
Sign up to set email alerts
|

The Hot Flush Behavior Scale

Abstract: Preliminary analysis of the HFBehS reveals it to be a psychometrically sound instrument. The HFBehS is grounded in women's experiences and can be used as a measure of behavioral reactions to HF/NS as well as enabling more rigorous evaluation of psychological interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 25 publications
(41 reference statements)
0
13
0
1
Order By: Relevance
“…These are assessed with the Behavior Short Form HFNS Beliefs and Behavior Scale, a 16 item scale that includes items from the Hot Flush Beliefs Scale [80] and the Hot Flush Behavior Scale [81], (Hunter, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…These are assessed with the Behavior Short Form HFNS Beliefs and Behavior Scale, a 16 item scale that includes items from the Hot Flush Beliefs Scale [80] and the Hot Flush Behavior Scale [81], (Hunter, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…Social attitudes may in turn influence an individual woman's views about menopause, as well as her appraisal of VMS (Rendall, Simmons, & Hunter, 2008). We have found that negative beliefs and appraisals of VMS and behavioural avoidance (e.g., avoiding social situations) were significantly associated with more problematic VMS (Hunter, Ayers, & Smith, 2011;Rendall et al, 2008;Reynolds, 2000). The three main types of negative beliefs and appraisals of VMS are:…”
mentioning
confidence: 95%
“…The Short Form Hot Flush Beliefs and Behaviours Scale (HFBBS) is a 16-item scale that includes items about beliefs and behaviours about hot flushes [ 19 ]. Subscales include: (i) beliefs about HF in social context (e.g.…”
Section: Methodsmentioning
confidence: 99%